Dimensions of the economic vote: Valence, positional and patrimony voting in Portugal's 2011 elections - Lobo, Marina Costa (2016)
This article contrasts three dimensions of economic voting, namely valence, positional and patrimony voting. Whereas the first two dimensions have been frequently explored, the patrimony variable has scarcely been tested as an explanatory variable of voting behaviour. It measures the electors' assets (both risky and non-risky), and seeks to capture the elector's wealth at election time. Using the 2011 post-election survey carried out in Portugal following the June elections, the data show that comparing of the three dimensions, valence is the most important. It was found that patrimony variables, although not significant in a comprehensive vote model, are important explanatory factors of party identification, itself a key variable of vote choice in Portugal.